Position transitions of polymer-grafted nanoparticles in diblock-copolymer nanocomposites (eXPRESS Polymer Letters)
Self-assembly of block copolymer/nanoparticle blends has promising applications in the design and fabrication of novel functional nanomaterials. Precise control of the spatial positions of nanoparticles within block copolymer-based nanomaterials is crucial to achieve some special physical properties and functions. Here, we employ the self-consistent field method to theoretically investigate the self-assembly of polymer grafted-nanoparticles in a diblock copolymer. It is found that by varying the size and selectivity of nanoparticles, one can not only produce various self-assembled nanostructures but also modulate the spatial positions of the nanoparticles, either at the copolymer interfaces or in the center of one copolymer phase, within the nanostructures. A denser grafted polymer brush plays a role of shielding effect on nanoparticles and can position them into the center of one copolymer phase. The nanostructural transition we observed is dictated by the competition between entropy and enthalpy. On the basis of a number of simulations, two phase diagrams of self-assembled nanostructures are constructed. This study may be helpful for optimal design of advanced materials with desired nanostructures and enhanced performance.